2021
DOI: 10.1038/s41598-021-01184-8
|View full text |Cite
|
Sign up to set email alerts
|

Offset of openings in optic nerve head canal at level of Bruch’s membrane, anterior sclera, and lamina cribrosa

Abstract: We compared the central retinal vascular trunk (CRVT) position, as a surrogate of lamina cribrosa (LC) offset, with the anterior scleral opening (ASCO) offset from the Bruch’s membrane opening (BMO). Based on the BMO-centered radial scans, the BMO and ASCO margins were demarcated, and each center was determined as the center of the best-fitted ellipse for each margin. The ASCO/BMO offset was defined as the offset between each center. Angular deviations and the extent of ASCO and CRVT offsets from the BMO cente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In this study, EOB presence differed according to the offset direction (Table 4): the EOB rarely existed in cases of inferior LC/BMO offset (Figure 3). This finding was in line with our previous study which demonstrated the difference between the LC/BMO and ASCO/BMO offsets (Lee et al, 2021a). This implies that the ASCO/BMO offset, which is visualized as the presence of EOB, would be an imperfect surrogate for LC/BMO offset, especially when its direction is towards the inferior side.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, EOB presence differed according to the offset direction (Table 4): the EOB rarely existed in cases of inferior LC/BMO offset (Figure 3). This finding was in line with our previous study which demonstrated the difference between the LC/BMO and ASCO/BMO offsets (Lee et al, 2021a). This implies that the ASCO/BMO offset, which is visualized as the presence of EOB, would be an imperfect surrogate for LC/BMO offset, especially when its direction is towards the inferior side.…”
Section: Discussionsupporting
confidence: 94%
“…Mismatch was associated with more negative CRVT angular deviation–inferotemporal CRVT (Table 3). We speculated that the LC/BMO offset would be smaller in that direction, as we have previously reported (Lee et al, 2021), which subsequently would lead to a higher probability of mismatch in PACG eyes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Visual signals are transferred to the brain via the retinal ganglion cells (RGCs), whose axons exit the eyeball through a gateway: the optic nerve head (ONH). The ONH being a three-dimensional (3D) structure with multiple layers, its morphology is determined by the offset of openings in different layers 1 7 . Offset is incurred as a result of expansion undergone by the eyeball during growth.…”
Section: Introductionmentioning
confidence: 99%